Efficient Synthesis of N-Phenyl-4-(trifluoromethyl)thiazol-2-amine and Its Antibacterial Activity - Tian, Xing; Zhang, Jin; Li, Yang (Synlett, 2025)
N-Phenyl-4-(trifluoromethyl) thiazole-2-amine is an important class of fluorinated heterocyclic compounds, particularly in the fields of fungicides and insecticides. However, there are very limited reports on the synthesis of such compounds. Here, we report a concise and efficient new method for synthesizing this thiazol-2-amine, which has good substrate versatility, strong functional group tolerance, and a single-product structure. The product structure and yield can be effectively and selectively controlled by adding or not adding alkali and other factors. Bactericidal activity tests showed that most of these compounds exhibit bactericidal activity, with the best bactericidal rate reaching 99%.
Keywords: trifluoromethyl; thiazole-2-amine; phenylthiourea; transition-metal free; bactericidal activity